Pengaruh Kompensasi, Beban Kerja, dan Pengembangan Karir Terhadap Turnover intention Karyawan Gen Z di Daerah Istimewa Yogyakarta - Ulviana, Ilah Fadhilah Dwi (Journal of Humanities Education Management Accounting and Transportation, 2025)
This research aims to analyze the influence of Compensation, Workload, and Career Development on Turnover intention of Gen Z D.I Yogyakarta Employees. The sample in this study was 96 respondents who were Gen Z employees in D.I Yogyakarta. The data collection technique used was a survey method with the research instrument used was a questionnaire. The results of the instrument test stated that the data in this study was proven to be valid and reliable. The Classical Assumption Test states that the data in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The results of the classical assumption test show that the data is normally distributed and produces a regression model that is free from heteroscedasticity and multicollinearity. The results of this research prove that: (1) Compensation has a positive and significant effect on the turnover intention of Gen Z D.I Yogyakarta employees, (2) Workload has a positive and significant effect on the turnover intention of Gen Z D.I Yogyakarta employees, (3) Career development has a negative and significant effect on the turnover intention of Gen Z D.I Yogyakarta employees, (4) Together compensation, workload and career development simultaneously influence the turnover intention of Gen Z D.I Yogyakarta employees. These results have implications for future researchers to examine factors that can cause turnover intention, especially in Gen Z who are starting to enter the world of work. The findings of this research have implications for companies to pay more attention to factors related to existing employees so that employee turnover intention does not occur.